Food losses from farm to retail operations: agricultural produces supply chain of Baja Peninsula, México (Agro Productividad, 2024)
Objective: To evaluate food losses (FL) volumes generated by farms in Baja California Peninsula, México, of five agricultural commodities. Design/methodology/approach: Baja California Sur (BCS) state was the study area. Information was gathered from a total of 380 sampled chain actors in asparagus, mango, strawberry, orange and tomato by survey and personal interviews. Tobit technique was applied to identify factors that influence FL percentage. Results: Data shows about 11.8% of asparagus is lost during harvesting and distribution, as well as 8.5% of strawberry, 26% of mango, 17.8% of oranges and 3.5% of tomatoes, representing 29.9% loss rate of marketed yield. Limitations on study/implications: This study did not classify commodities in the last steps of the supply chain. The five commodities used in the current study correspond to the more important agricultural produces in BCS, but given changing market, harvesting time and produce availability did not consider the waste of the supply chain. Findings/conclusions: Commodity, type of transportation and distribution, education, and human resources has been identified as influence factors in the volume of FL. This exploratory study fills the void in information in terms of its geographic scope and food group number, and farm owners willing to manage food losses for the purpose of obtaining bioactive compound.